Effects of FK228, a novel histone deacetylase inhibitor, on human lymphoma U-937 cells in vitro and in vivo - Sasakawa, Yuka; Naoe, Yoshinori; Inoue, Takeshi; Sasakawa, Tatsuya; Matsuo, Masahiko; Manda, Toshitaka; Mutoh, Seitaro (Biochemical pharmacology, 2002)
FK228 [( E)-(1 S,4 S,10 S,21 R)-7-[( Z)-ethylidene]-4,21-diisopropyl-2-oxa-12,13-dithia-5,8,20,23-tetraazabicyclo-[8,7,6]-tricos-16-ene-3,6,9,19,22-pentanone; FR901228, depsipeptide] is a novel histone deacetylase inhibitor that shows therapeutic efficacy in Phase I trials of patients with malignant lymphoma. However, its mechanism of action has not been characterized. In this study, we examined the in vitro and in vivo effects of FK228 on human lymphoma U-937 cells. FK228 very strongly inhibited the growth of U-937 cells with an ic 50 value of 5.92 nM. In a scid mouse lymphoma model, mice treated with FK228 once or twice a week survived longer than control mice, with median survival times of 30.5 (0.56 mg/kg) and 33 days (0.32 mg/kg), respectively (vs. 20 days in control mice). Remarkably, 2 out of 12 mice treated with FK228 (0.56 mg/kg once or twice a week) survived past the observation period of 60 days. The apoptotic population of U-937 cells time-dependently increased to 37.7% after 48 hr of treatment with FK228. In addition, FK228 induced G1 and G2/M arrest and the differentiation of U-937 cells to the CD11b +/CD14 + phenotype. Expression of p21 WAF1/Cip1 and gelsolin mRNA increased up to 654- and 152-fold, respectively, after 24 hr of treatment with FK228. FK228 caused histone acetylation in p21 WAF1/Cip1 promoter regions, including the Sp1-binding sites. In conclusion, (i) FK228 prolonged the survival time of scid mice in a lymphoma model, and (ii) the beneficial effects of FK228 on human lymphoma may be exerted through the induction of apoptosis, cell cycle arrest, and differentiation via the modulation of gene expression by histone acetylation.